Dual endothelin antagonist aprocitentan for resistant hypertension (PRECISION): a multicentre, blinded, randomised, parallel-group, phase 3 trial. Issue 10367 (3rd December 2022) - Schlaich, Markus P; Bellet, Marc; Weber, Michael A; Danaietash, Parisa; Bakris, George L; Flack, John M; Dreier, Roland F; Sassi-Sayadi, Mouna; Haskell, Lloyd P; Narkiewicz, Krzysztof; Wang, Ji-Guang; ,; et al.
Summary: Background: Resistant hypertension is associated with increased cardiovascular risk. The endothelin pathway has been implicated in the pathogenesis of hypertension, but it is currently not targeted therapeutically, thereby leaving this relevant pathophysiological pathway unopposed with currently available drugs. The aim of the study was to assess the blood pressure lowering efficacy of the dual endothelin antagonist aprocitentan in patients with resistant hypertension. Methods: PRECISION was a multicentre, blinded, randomised, parallel-group, phase 3 study, which was done in hospitals or research centres in Europe, North America, Asia, and Australia. Patients were eligible for randomisation if their sitting systolic blood pressure was 140 mm Hg or higher despite taking standardised background therapy consisting of three antihypertensive drugs, including a diuretic. The study consisted of three sequential parts: part 1 was the 4-week double-blind, randomised, and placebo-controlled part, in which patients received aprocitentan 12·5 mg, aprocitentan 25 mg, or placebo in a 1:1:1 ratio; part 2 was a 32-week single (patient)-blind part, in which all patients received aprocitentan 25 mg; and part 3 was a 12-week double-blind, randomised, and placebo-controlled withdrawal part, in which patients were re-randomised to aprocitentan 25 mg or placebo in a 1:1 ratio. The primary and key secondary endpoints were changes in unattended office systolic blood pressure from baseline to week 4 and from withdrawal baseline to week 40, respectively. Secondary endpoints included 24-h ambulatory blood pressure changes. The study is registered on ClinicalTrials.gov, NCT03541174 . Findings: The PRECISION study was done from June 18, 2018, to April 25, 2022. 1965 individuals were screened and 730 were randomly assigned. Of these 730 patients, 704 (96%) completed part 1 of the study; of these, 613 (87%) completed part 2 and, of these, 577 (94%) completed part 3 of the study. The least square mean (SE) change in office systolic blood pressure at 4 weeks was –15·3 (SE 0·9) mm Hg for aprocitentan 12·5 mg, –15·2 (0·9) mm Hg for aprocitentan 25 mg, and –11·5 (0·9) mm Hg for placebo, for a difference versus placebo of –3·8 (1·3) mm Hg (97·5% CI –6·8 to –0·8, p=0·0042) and –3·7 (1·3) mm Hg (–6·7 to –0·8; p=0·0046), respectively. The respective difference for 24 h ambulatory systolic blood pressure was –4·2 mm Hg (95% CI –6·2 to –2·1) and –5·9 mm Hg (–7·9 to –3·8). After 4 weeks of withdrawal, office systolic blood pressure significantly increased with placebo versus aprocitentan (5·8 mm Hg, 95% CI 3·7 to 7·9, p<0·0001). The most frequent adverse event was mild-to-moderate oedema or fluid retention, occurring in 9%, 18%, and 2% for patients receiving aprocitentan 12·5 mg, 25 mg, and placebo, during the 4-week double-blind part, respectively. This event led to discontinuation in seven patients treated with aprocitentan. During the trial, a total of 11 treatment-emergent deaths occurred, none of which were regarded by the investigators to be related to study treatment. Interpretation: In patients with resistant hypertension, aprocitentan was well tolerated and superior to placebo in lowering blood pressure at week 4 with a sustained effect at week 40. Funding: Idorsia Pharmaceuticals and Janssen Biotech.